Quantum Correlations in Fiber Links of the Recife Quantum Network - Oliveira, Nallyson W. S.; Siqueira, André C. A.; Crisóstomo, Gabriel A.; Martins, Paulo; Freitas, Leandro L. L.; Almeida, Alexandre A. C. de; Acioli, Lúcio H.; Coelho, Leonardo D.; Ferraz, José; Martins-Filho, Joaquim F.; Felinto, Daniel (Anais do Workshop de Redes Quânticas (WQuNets), 2026)
This work presents the experimental characterization of quantum correlations in optical fiber links of the Recife Quantum Network using a type-II SPDC photon-pair source operating at 800 nm. The analysis is based on the normalized cross-correlation function g (2) 12 , used to quantify temporal correla tions between signal and idler photons. One photon of each pair is transmitted through the network in a loop configuration, while its partner is detected locally. The results show that quantum correlations are preserved after propagation through urban optical fibers, despite attenuation and environmental noise. These findings demonstrate the potential of the infrastructure for quantum communication experiments, including quantum key distribution (QKD), in urban-scale networks.